An Investigation of the Determinants of Self-Employment: A Mediation of Entrepreneurial Motivation in Bauchi State, Nigeria - Muhammad, Adamu (Universiti Malaysia Sarawak(UNIMAS), 2018)
Self-employment is becoming more dominant topic due to the persistent prevalence of unemployment issues in Nigeria. Thus, the aim of this research is to conduct an investigation of the determinants of self-employment and the mediating role of entrepreneurial motivation among potential entrepreneurs in Bauchi State, Nigeria. This study employed quantitative technique through a cross-sectional survey where questionnaires were distributed and primary data were collected for the study. Through the analysis using PLS-SEM, the study findings suggested that the independent variables namely; transformationality, resilience, autonomy, machinery/equipment, vocational training, ICT, taxation incentives, financing and entrepreneurial motivation as a mediating variable significantly influences self-employment. Hence, these stimulate the potential entrepreneurs to make persistent and intense efforts in their pursuit for the accomplishment of self-employment. This study incorporates some less-researched factors (some other dimensions of entrepreneurial traits, economic incentive factors and entrepreneurial motivation) that influence self-employment. Furthermore, this study theoretically incorporates three theories (i.e. the vroom expectancy motivation theory, the personality trait theory and the economic entrepreneurship theory) especially in developing the conceptual framework for the study. The novelty of this study lies in the merging of the selected theories to develop the research framework. Other than that, exploring the under- researched factors of self-employment determinants in the context of Nigeria also added value to self-employment literature.